ANALISIS PENGARUH DANA PIHAK KETIGA DAN TINGKAT BAGI HASIL TERHADAP PEMBIAYAAN PADA PT. BANK MUAMALAT INDONESIA.Tbk CABANG MEDAN - Affan Syu’aidi (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2017)
The main activity of the bank is to mobilize funds from the public for further distribution to individuals or institutions in the form of loans for various purposes. In this case, Bank Muamalat Branch Medan issued a financing product with Islamic principles. The purpose of this study to verify the influence of third party funds and influence the profit sharing to finance at Bank Muamalat Branch Medan by using multiple regression analysis. The data used is data per quarter from the first quarter of 2009 until the fourth quarter of 2016. Data collection technique used documentation study to look at the financial report of Bank Muamalat Branch Medan. The results were obtained with an alpha level of 5%, which showed that partially fund a third party and the level of revenue sharing positively affect financing in Bank Muamalat Branch Medan.